2020
DOI: 10.9734/ajsspn/2020/v6i330092
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Salt Affected Soils and Improvement of Rice and Wheat Yields by Adding Compost and Foliar Spray of Zinc, Potassium and Compost Tea

Abstract: Amelioration of salt-affected soils requires an integrated management approach, by eco-friendly environmental methods which help improve soil properties, increases crop yield and quality.  Hence, a study was done to evaluate the performances of combined use of compost and foliar application of Zn, K and compost tea. In salt affected soil in the rice-wheat system. A field experiment at El Hamool district, Kafr El Sheikh governorate, Egypt was carried out during 2019 summer for rice and 2020 winter season for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Concerning the impact of the treatments on soil chemical properties as pH, EC e and ESP (%), the impacts were in the following order: compost + gypsum ˃ gypsum ˃ compost ˃ control in both growing seasons. These results supported by [13,43] who found that application of gypsum followed by a mature municipal solid compost mix has been used to restore degraded sodic soils. Similarly, [44] reported that gypsum was effective in the reclamation of sodic soils.…”
Section: Soil Chemical Propertiessupporting
confidence: 82%
See 4 more Smart Citations
“…Concerning the impact of the treatments on soil chemical properties as pH, EC e and ESP (%), the impacts were in the following order: compost + gypsum ˃ gypsum ˃ compost ˃ control in both growing seasons. These results supported by [13,43] who found that application of gypsum followed by a mature municipal solid compost mix has been used to restore degraded sodic soils. Similarly, [44] reported that gypsum was effective in the reclamation of sodic soils.…”
Section: Soil Chemical Propertiessupporting
confidence: 82%
“…This may be reflected the role of compost in increasing the soil aggregation, increasing the soil porosity and decreasing soil bulk density as well as improving soil properties [7,12], treatment of compost + gypsum was more pronounced the other treatment due the role of gypsum and compost on improvement the chemical and physical of the soil properties this results are supported by [2,13]. With respect to the effect of foliar application of compost tea or proline on soil bulk density and total porosity after harvesting of rice yield, data pointed out that soil bulk density and total porosity were nonsignificant effect in both seasons as shown in Table 4.On the other hand the soil bulk density and total porosity were non-significant affected by the inter action between the all treatment.…”
Section: Soil Bulk Density (Bd) and Total Porositymentioning
confidence: 70%
See 3 more Smart Citations